Structural, physicochemical properties, and resistant starch content of autoclaved arenga starch (Arenga pinnata (Wurmb) Merr) - Nani Ratnaningsih; Novita Intan Arovah (Food Chemistry Advances)
Autoclaving-cooling (AC) has been proven to increase resistant starch content and thermal stability of various starches; however, its application to arenga starch (Arenga pinnata (Wurmb) Merr) remains underexplored. The objective of study was to investigate the structural, physicochemical properties, and resistant starch (RS) content of arenga starch by one, two, and three cycles of AC. AC treatment modified arenga starch into a compact structure and increased particle size from 18.90±0.02 μm to 32.49±0.08 μm. The highest amylose and RS content were found in two cycles of autoclaved arenga starch (AAS2) from 52.11±0.21 % to 60.72±0.48 % and 17.10±0.11 % to 22.54±0.49 % (p < 0.05), respectively. Insoluble and total dietary fiber increased by 48.21 % and 15.25 % (p < 0.05), respectively. Water and oil holding capacities, peak time, and setback viscosity were enhanced; however, swelling power, pasting temperature, peak viscosity, and gelatinization enthalpy of AAS were lower than their native (p < 0.05). AC treatment shifted the crystalline structure from CA-type to a combination of B + V-types. AC treatment reduced the degree of double helix and degree of order of AAS; however, it promoted the formation of a single helix V-type structure and a structural transformation. AAS2 could be developed as a functional ingredient with higher RS content and better thermal stability.